2019
DOI: 10.3390/su11216105
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Restaurant Social Media on Environmental Sustainability: An Empirical Study

Abstract: Social media is currently a powerful way for companies to keep in touch with their customers and promote new products. The main objective of this research paper is to analyze the impact of social media marketing on environmental sustainability in food and beverage service companies in Spain, taking customer satisfaction into account. The variables, such as customer trust, perceived value, and continuance intention, were also studied to determine whether they influence environmental sustainability. In order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 115 publications
1
51
0
1
Order By: Relevance
“…In this relation, the contributions to this Special Issue have different areas of specialization within the indicated strategies for the sustainable development of companies in digital environments. In the first place, digital business models are studied to understand how their viability and profitability are sometimes based on the good use of the information that companies obtain from the Internet and the analysis of their strategies [3].…”
Section: Introductionmentioning
confidence: 99%
“…In this relation, the contributions to this Special Issue have different areas of specialization within the indicated strategies for the sustainable development of companies in digital environments. In the first place, digital business models are studied to understand how their viability and profitability are sometimes based on the good use of the information that companies obtain from the Internet and the analysis of their strategies [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the 21st century, social media have become a new way of communication that enables people to obtain information and express their beliefs and ideas in a new way [ 29 ]. Social platforms, such as Facebook, Twitter, YouTube, Instagram, or LinkedIn, have entered people’s daily lives; today, people increasingly use these media for social interaction and information exchange [ 30 , 31 ]. Nowadays, social media are used in different fields like culture, entertainment, education, politics, economy, or business.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this connection, a study by Pereira-Moliner et al [ 60 ] showed that environmental management practices positively influence financial performance, market success, and the satisfaction of users and employees. However, few studies directly explored the relationship between environmental sustainability and user satisfaction [ 31 ]. Based on the considerations discussed above, the following hypothesis can be formulated:…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…ORs provide consumers with relevant information which derives from different sources and is aimed at different goals: informative reviews give additional product information from the user's perspective, such as attributes, characteristics, and performance; recommendation reviews provide positive or negative evaluations of the product; and numerical ratings assign numerical values to a set of attributes considered relevant, based on the postconsumer user experience. With this information, potential customers create expectations and attitudes towards the consumption of the product or experience [5,8,27]. Despite its usefulness, ORs are not free from criticism.…”
Section: Relevance Of Crws On Consumers' Behaviormentioning
confidence: 99%
“…Among the various existing instruments, Consumer Review Websites (CRWs) such as TripAdvisor, Booking, or Yelp have recently grown in importance [8][9][10]. CRWs enable consumers to write online reviews (ORs), which consist of a quantitative (as a score) and/or a qualitative recommendation (as an opinion) on certain aspects of the tourism experience and also on the experience as a whole.…”
Section: Introductionmentioning
confidence: 99%